Evolution models of helium white dwarf–main-sequence star merger remnants: the mass distribution of single low-mass white dwarfs. Issue 1 (24th October 2017) - Zhang, Xianfei; Hall, Philip D.; Jeffery, C. Simon; Bi, Shaolan
Abstract: It is not known how single white dwarfs with masses less than 0.5 M⊙ – low-mass white dwarfs – are formed. One way in which such a white dwarf might be formed is after the merger of a helium-core white dwarf with a main-sequence star that produces a red giant branch star and fails to ignite helium. We use a stellar evolution code to compute models of the remnants of these mergers and find a relation between the pre-merger masses and the final white dwarf mass. Combining our results with a model population, we predict that the mass distribution of single low-mass white dwarfs formed through this channel spans the range 0.37–0.5 M⊙ and peaks between 0.45 and 0.46 M⊙ . Helium white dwarf–main-sequence star mergers can also lead to the formation of single helium white dwarfs with masses up to 0.51 M⊙ . In our model, the Galactic formation rate of single low-mass white dwarfs through this channel is about 8.7 × 10 −3  yr −1 . Comparing our models with observations, we find that the majority of single low-mass white dwarfs (≤0.5 M⊙ ) are formed from helium white dwarf–main-sequence star mergers, at a rate which is about 2 per cent of the total white dwarf formation rate.